PENGUATAN RUANG KEAGAMAAN BERBASIS KAPITAL SOSIAL DI DESA BABADAN KECAMATAN NGRAMBE KABUPATEN NGAWI - Mudzakkir; Moh. Irmawan Jauhari (Universitas Islam Tribakti (UIT) Lirboyo Kediri, 2022)
The purpose of this activity is to follow up on the social mapping that has been done before and to oversee the KKN program that is recommended. Where strengthening the religious area is one of the main points apart from strengthening the educational area in Babadan Village, Ngrambe District, Ngawi Regency. This service activity uses the ABCD which prioritizes the utilization of assets and potential in the community. ABCD requires other tools for operational definition namely; Problem Based Approach, Need Based Approach, Right Based Approach, Asset Based Approach. The result is the strengthening of social resilience-based religious space in Babadan Village, Ngrambe Subdistrict, Ngawi Regency focusing on three activities namely the yasin congregation ladies and gentlemen, hadrah training for mothers, and improving the quality of TPQ ustadz. These three activities are supported by the social capital of the Babadan community and external stakeholders. Strengthening religious space based on social capital in Babadan Village, Ngrambe District, Ngawi Regency takes into account internal capabilities and also external community support.